2022
DOI: 10.1055/s-0042-1744549
|View full text |Cite
|
Sign up to set email alerts
|

Improving COVID-19 Research of University Hospitals in Germany: Formative Usability Evaluation of the CODEX Feasibility Portal

Abstract: Background Within the German “Network University Medicine,” a portal is to be developed to enable researchers to query on novel coronavirus disease 2019 (COVID-19) data from university hospitals for assessing the feasibility of a clinical study. Objectives The usability of a prototype for federated feasibility queries was evaluated to identify design strengths and weaknesses and derive improvement recommendations for further development. Methods In the course of a remote usability test with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…A usability analysis of our prototype revealed that it is simple and intuitive. It also showed 26 problems, 8 of which were rated as “critical” [ 33 ]. However, usability problems were focused on the presentation of the UI or the ontology and will have no impact on the architectural decisions made.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A usability analysis of our prototype revealed that it is simple and intuitive. It also showed 26 problems, 8 of which were rated as “critical” [ 33 ]. However, usability problems were focused on the presentation of the UI or the ontology and will have no impact on the architectural decisions made.…”
Section: Resultsmentioning
confidence: 99%
“…As part of our project, we performed a usability analysis based on our prototype implementation of the UI, the results of which were fed back into our development process to improve the user experience. This evaluation is described in more detail in a separate publication [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Für die Erhebung der Daten, die bisher noch nicht Bestandteil der elektronischen Krankenakte waren, wurden Datenerfassungssysteme (REDCap und DIS) mit standardisierten Data Dictionaries und einem vordefinierten Extraktionsprozess zur Generierung der FHIR-GECCO-Formate bereitgestellt. Für föderierte Machbarkeitsabfragen wurden diese FHIR-Server über zentral entwickelte Komponenten und sichere Datenverbindungen an ein Abfrageportal zur klinischen Charakterisierung von COVID-19-Patient*innen angebunden [ 6 8 ]. Auf Basis dieser dezentralen COVID-19-Forschungsdatenrepositorien konnten wissenschaftliche Erkenntnisse zum Verlauf der COVID-19-Pandemie und zu ihren Auswirkungen auf die stationäre Versorgung in den UK bereits im Sommer 2020 gewonnen werden [ 9 – 11 ].…”
Section: Die Fünf Komponenten Der Num-forschungsdateninfrastrukturunclassified
“…We reviewed other existing COVID data efforts across the world [81][82][83][84][85][86]. Most projects focus on the analysis of data sets that were already known to the researchers, whereas CO-CONNECT (as well as CODEX [84,85]) also provides the capability to search for specific cohorts of data for feasibility analysis across population-wide data.…”
Section: Comparison With Other International Covid-19 Initiativesmentioning
confidence: 99%